‘Are we getting through to them? And in what way?’ Communicating physical activity with adolescents - Grady, Caera L.; Murtagh, Elaine; Ng, Kwok; García Bengoechea, Enrique; Woods, Catherine B. (Oxford University Press (OUP), 2025)
The Active School Flag (ASF) is a multi-stage, multi-component, whole-of-school physical activity (PA) programme. This study explored relationships between Irish adolescents' health literacy, PA knowledge, beliefs and awareness and their efforts to communicate PA messages. Schools (n = 17) newly enrolled in the ASF programme were invited to participate in a mixed methods study. A questionnaire assessing adolescents' health literacy, PA knowledge and beliefs about the consequences of behaviour, and ASF programme awareness was completed in five schools. Statistical analysis involved a hierarchical multiple linear regression. Focus groups (n = 11) were conducted with ASF programme implementers in ten schools to understand current practices of communicating PA messages. Data were analysed using a reflexive thematic analysis. Males comprised 62.3% of the sample (N = 483), and 57.1% were junior students (1st-3rd year). The overall model significantly predicted adolescents' health literacy, F(4, 464) = 56.241, P < .001. Gender (B = -1.09, P = .02), knowledge of PA (B = 0.4, P = .04), and beliefs about the consequences of behaviour (B = 2.3, P < .001) were significant predictors of health literacy, accounting for 33.2% of the variance. Challenges included low awareness of, engagement with, and maximizing support for implementing ASF. The gap identified between the messages communicated and awareness of ASF requires further research to develop an effective, structured, and standardized PA communication plan for schools to facilitate policy and practice. Improving adolescents' knowledge and beliefs about the consequences of PA could improve overall health literacy levels. Therefore, providing support and guidance to whole-of-school programme implementers for communicating PA messages will help influence practice and policy.